Progressives, Patterns, Pedagogy. A corpus-driven approach to English progressive forms, functions, contexts and diadactic - Mindt, Ilka; Römer, Ute (Anglistik. International Journal of English Studies, 19, 2)

Corpus Linguistics 25 Years on. (Language and Computers: Studies in Practical Linguistics 62) - Mindt, Ilka; Facchinetti, Roberta (ICAME Journal, Computers in English Linguistics, 2008)

The Kinetic Facility Location Problem - Degener, Bastian; Gehweiler, Joachim; Lammersen, Christiane (Proceedings of the 11th Scandinavian Workshop on Algorithm Theory (SWAT))

The Kinetic Facility Location Problem - Gehweiler, Joachim; Lammersen, Christiane; Degener, Bastian (Proceedings of the 24th European Workshop on Computational Geometry)
We present a deterministic kinetic data structure for the facility location problem that maintains a subset of the moving points as facilities such that, at any point of time, the sum of the maintenance cost for the facilities and the connection cost for the clients is at most a constant factor larger than the current optimal cost. In our scenario, each point can open a facility and moves continuously along a known trajectory in a d-dimensional Euclidean space where d is a constant. Our kinetic data structure has a storage requirement of O(n (log^d(n)+log(nR))), where n is the number of points and R is the ratio of the product of the maximum maintenance cost and demand to the product of their corresponding minimum values. In the case that each trajectory can be described by a bounded degree polynomial, the data structure processes O(n^2 log^2(nR)) events, each requiring only O(log(nR)) facility changes and O(log^(d+1)(n) log(nR)) time. This results in a total processing time of O(n^2 log^(d+1)(n) log^3(nR)). To the best of our knowledge, this is the first kinetic data structure for the facility location problem.

„Kulturelles Erbe: Denkmalpflege, Restaurierung, Authentizität, Wiederaufbau“ - Seng, Eva- Maria (ForschungsForumPaderborn)

„Modern oder gothisch – gothisch und antique römische Architectur vermischt“ – die Vorschläge zu Wiederaufbau und Rekonstruktion des Speyrer Doms 1771 - Seng, Eva- Maria (Reibungspunkte. Ordnung und Umbruch in Architektur und Kunst. Festschrift zum 65. Geburtstag von Hubertus Günther)

„… Der Hauptzweck ist, die große Welt … allhier im kleineren beisammen zu haben“. Kunst- und Wunderkammern als Bildungseinrichtungen - Seng, Eva- Maria (Hallesche Beiträge zur Europäischen Aufklärung)

Der nahe Spiegel. Vormärz und Aufklärung

Thomas Valentin Lesebuch (Edition) - Eke, Norbert Otto; Olasz-Eke, Dagmar

An O(log n) dominating set protocol for wireless ad-hoc networks under the physical interference model - Scheideler, Christian; W. Richa, Andréa; Santi, Paolo (Proceedings of the 9th ACM Interational Symposium on Mobile Ad Hoc Networking and Computing, MobiHoc 2008, Hong Kong, China, May 26-30, 2008)

Humus Büchner: Dantons Tod in/und Heiner Müllers Der Auftrag - Eke, Norbert Otto (Büchner Jahrbuch 11 (2005-08))

„Gott schütz uns vor den guten Menschen“. Reinigungsrituale und Beschämungsstrategien im deutsch-jüdischen Verhältnis - Eke, Norbert Otto (Schuld und Scham)

„Aber die Liebe? Aber der Tod?“ Judith Kuckarts Prosa - Eke, Norbert Otto (Literatur in Westfalen. Beiträge zur Forschung 9)

Geschichtsprojektionen. Rekurse auf das 18. Jahrhundert und die Konstruktion von ‚Aufklärung’ im deutschen Vormärz - Eke, Norbert Otto; Bunzel, Wolfgang; Vaßen, Florian (Der nahe Spiegel. Vormärz und Aufklärung)

„Man muß die Deutschen mit der Novelle fangen“. Theodor Mundt, die Poesie des Lebens und die „Emancipation der Prosa“ im Vormärz - Eke, Norbert Otto (Der nahe Spiegel. Vormärz und Aufklärung)

„Auf des Degens Spitze die Welt jetzt steht“. Heiner Müller liest Schiller - Eke, Norbert Otto („Verteufelt human“? Zum Humanitätsideal der Weimarer Klassik)

Orient und Okzident. Mohammed, der Islam und das Christentum. Zur Darstellung kultureller Alterität um 1800 (mit einem Seitenblick auf die Bestände der Fürstlichen Bibliothek Corvey) - Eke, Norbert Otto (Der Deutschen Morgenland. Bilder des Orients in der deutschen Literatur und Kultur von 1770-1850)

„In jeder Sprache sitzen andere Augen“. Herta Müllers ex-zentrisches Schreiben - Eke, Norbert Otto (Unterwegs. Zur Poetik des Vagabundentums im 20. Jahrhundert)

Nachwort - Eke, Norbert Otto; Olasz-Eke, Dagmar (Thomas Valentin Lesebuch. Zusammengestellt und mit einem Nachwort von Norbert Otto Eke und Dagmar Olasz-Eke)

Algorithms for Overlay Networks - Scheideler, Christian (Bulletin of the EATCS)

A jamming-resistant MAC protocol for single-hop wireless networks - Awerbuch, Baruch; W. Richa, Andréa; Scheideler, Christian (Proceedings of the Twenty-Seventh Annual ACM Symposium on Principles of Distributed Computing, PODC 2008, Toronto, Canada, August 18-21, 2008)

SPREAD: an adaptive scheme for redundant and fair storage in dynamic heterogeneous storage systems - Mense, Mario; Scheideler, Christian (Proceedings of the Nineteenth Annual ACM-SIAM Symposium on Discrete Algorithms, SODA 2008, San Francisco, California, USA, January 20-22, 2008)

Tiara: A Self-stabilizing Deterministic Skip List - Clouser, Thomas; Nesterenko, Mikhail; Scheideler, Christian (Stabilization, Safety, and Security of Distributed Systems, 10th International Symposium, SSS 2008, Detroit, MI, USA, November 21-23, 2008. Proceedings)

Broadcasting: Wie verbreite ich schnell Informationen? - Scheideler, Christian (Taschenbuch der Algorithmen)

INFORMATIK 2008, Beherrschbare Systeme - dank Informatik, Band 1, Beiträge der 38. Jahrestagung der Gesellschaft für Informatik e.V. (GI), 8. - 13. September, in München, Deutschland

Taschenbuch der Algorithmen - Vöcking, Berthold; Alt, Helmut; Dietzfelbinger, Martin; Reischuk, Rüdiger; Scheideler, Christian; Vollmer, Heribert; Wagner, Dorothea

Redundant Data Placement Strategies for Cluster Storage Environments - Brinkmann, André; Effert, Sascha (Proc. Int. Conf. on Principles Of DIstributed Systems (OPODIS))

Employing WS-BPEL Design Patterns for Grid Service Orchestration using a Standard WS-BPEL Engine and a Grid Middleware - Brinkmann, André; Gudenkauf, Stefan; Hasselbring, Wilhelm; Höing, André; Karl, Holger; Kao, Odej; Nitsche, Holger; Scherp, Guido (Proc. Cracow Grid Workshop (CGW))

Virtual Supercomputer for HPC and HTC - Birkenheuer, Georg; Brinkmann, André; Dömer, Hubert; Effert, Sascha; Konersmann, Christoph; Niehörster, Oliver; Simon, Jens (Proc. Gemeinsamer Workshop der GI/ITG Fachgruppen "Betriebssysteme" und "KuVS": Virtualized IT infrastructures and their management)

A method for OSEM PET reconstruction on parallel architectures using STIR - Beisel, Tobias; Lietsch, Stefan; Thielemans, Kris (IEEE Nuclear Science Symposium Conference Record (NSS))

Guarantee and Penalty Clauses for Service Level Agreements - Battré, Dominic; Birkenheuer, Georg; Deora, Vikas; Hovestadt, Matthias; Rana, Omer; Wäldrich, Oliver (Proc. Cracow Grid Workshop (CGW))

Layered understanding for sporadic imitation in a multi-robot scenario - Richert, Willi; Niehörster, Oliver; Koch, Markus (Proc. IEEE/RSJ Int.Conf. on Intelligent Robots and Systems (IROS))

Proc. Int. Workshop on Storage Network Architecture and Parallel I/Os (SNAPI)

Computational Steering Of Interactive Material Flow Simulations - Lietsch, Stefan; Zabel, Henning; Laroque, Christoph (Proc. ASME Computers and Information in Engineering Conference (CIE))

The GOmputer: Accelerating GO with FPGAs - Platzner, Marco; Döhre, Sven; Happe, Markus; Kenter, Tobias; Lorenz, Ulf; Schumacher, Tobias; Send, Andre; Warkentin, Alexander (Proc. Int. Conf. on Engineering of Reconfigurable Systems and Algorithms (ERSA))

CUDA-based, parallel JPEG Compression for Remote Rendering - Lietsch, Stefan; Hermann Lensing, Paul (Proc. Int. Symp. on Image/Video Communications over fixed and mobile networks (ISVC))

Overbooking in Planning Based Scheduling Systems - Birkenheuer, Georg; Hovestadt, Matthias; Kao, Odej; Voß, Kerstin (Proc. Int. Conf. on Grid Computing & Applications (GCA))

Data Replication in P2P Environments - Brinkmann, André; Effert, Sascha (Proc. Int. Symp. on Parallelism in Algorithms and Architectures (SPAA))

SelfS – A Real-Time Protocol for Virtual Ring Topologies - Griese, Björn; Brinkmann, André; Porrmann, Mario (Proc. Int. Symp. on Parallel and Distributed Processing (IPDPS))

Recursive Evaluation of Fault Tolerance Mechanisms for SLA Management - Voss, Kerstin (Proc. Int. Conf. on Networking and Services (ICNS))

Proceedings of the 1. GI/ITG KuVS Fachgespräch Virtualisierung

Storage Cluster Architectures - Brinkmann, André; Effert, Sascha (Proc. of the GI/ITG KuVS Fachgespr ̈ach Virtualisierung)

Guiding exploration by combining individual learning and imitation in societies of autonomous robots - Richert, Willi; Klompmaker, Florian; Niehörster, Oliver (Proc. IFIP Conf. on Biologically Inspired Cooperative Computing (BICC))

GPU-Supported Image Compression for Remote Visualization - Realization and Benchmarking - Lietsch, Stefan; Hermann Lensing, Paul (Proc. Int. Symp. on Visual Computing (ISVC))

Computational Steering verteilter, interaktiver Materialflusssimulationen - Laroque, Christoph; Lietsch, Stefan; Zabel, Henning (Augmented & Virtual Reality in der Produktentstehung)

Degree 3 Suffices: A Large-Scale Overlay for P2P Networks - Bienkowski, Marcin; Brinkmann, André; Korzeniowski, Miroslaw (Proc. Int. Conf. on Principles Of DIstributed Systems (OPODIS))

Applying Risk Management to Support SLA Provisioning - Battre, Dominic; Birkenheuer, Georg; Hovestadt, Matthias; Kao, Odej; Voss, Kerstin (Proc. Cracow Grid Workshop (CGW))

Implementing WS-Agreement in a Globus Toolkit 4.0 Environment - Battré, Dominic; Kao, Odej; Voss, Kerstin (Proc. Usage of Service Level Agreements in Grids Workshop held in conjunction with International Conference on Grid Computing)

Aggregating Robots Compute: An Adaptive Heuristic for the Euclidean Steiner Tree Problem - Hamann, Heiko; Wörn, Heinz (The tenth International Conference on Simulation of Adaptive Behavior (SAB'08))

Spatial Macroscopic Models of a Bio-Inspired Robotic Swarm Algorithm - Hamann, Heiko; Schmickl, Thomas; Wörn, Heinz; Crailsheim, Karl (IEEE/RSJ 2008 International Conference on Intelligent Robots and Systems (IROS'08))
We present a comparative study of two spatially resolved macroscopic models of an autonomous robotic swarm. In previous experiments, the collective behavior of 15 autonomous swarm robots, driven by a simple bio-inspired control algorithm, was investigated: in two different environmental conditions, the ability of the robots to aggregate below a light source was tested. Distinct approaches to predict the dynamics of the spatial distribution were made by two different modeling approaches: one model was constructed in a compartmental manner (ODEs). In parallel, a space-continuous model (PDEs) was constructed. Both models show a high degree of similarity concerning the modeling of concrete environmental factors (light), but due to their different basic approaches, show also significant differences in their implementation. However, the predictions of both models compare well to the observed behavior of the robotic swarm, thus both models can be used to develop further extensions of the algorithm as well as different experimental setups without the need to run extensive real robotic preliminary experiments.